P-wave morphology and the risk of incident ischemic stroke in the Multi-Ethnic Study of Atherosclerosis - Kamel, Hooman; Soliman, Elsayed Z; Heckbert, Susan R; Kronmal, Richard A; Longstreth, Jr, W T; Nazarian, Saman; Okin, Peter M (Stroke (1970), 2014)
Emerging data suggest that left atrial disease may cause ischemic stroke in the absence of atrial fibrillation or flutter (AF). If true, this condition may provide a cause for many strokes currently classified as cryptogenic. Among 6741 participants in the Multi-Ethnic Study of Atherosclerosis who were free of clinically apparent cerebrovascular or cardiovascular disease (including AF) at baseline, we examined the association between markers of left atrial abnormality on a standard 12-lead ECG-specifically P-wave area, duration, and terminal force in lead V1-and the subsequent risk of ischemic stroke while accounting for incident AF. During a median follow-up of 8.5 years, 121 participants (1.8%) had a stroke and 541 participants (8.0%) were diagnosed with AF. In Cox proportional hazards models adjusting for potential baseline confounders, P-wave terminal force in lead V1 was more strongly associated with incident stroke (hazard ratio per 1 SD increase, 1.21; 95% confidence interval, 1.02-1.44) than with incident AF (hazard ratio per 1 SD, 1.11; 95% confidence interval, 1.03-1.21). The association between P-wave terminal force in lead V1 and stroke was robust in numerous sensitivity analyses accounting for AF, including analyses that excluded those with any incident AF or modeled any incident AF as having been present from baseline. We found an association between baseline P-wave morphology and incident stroke even after accounting for AF. This association may reflect an atrial cardiopathy that leads to stroke in the absence of AF.